Pemanfaatan AI (Artificial Intelligence) dalam Penulisan Karya Ilmiah bagi Mahasiswa - Supriyono, Areni Yulitawati; Rumalean, Iwan; Triyana, Eka; Kurniawan, Sabda Aji; Juwanda, Juwanda (Universitas Pattimura, 2025)
Students' need for efficiency in writing scientific papers is increasingly urgent, along with the increasing academic demands and complexity of research in various fields. Amidst busy schedules, students are often faced with the pressure to produce high-quality work in a limited amount of time. This prompts the search for solutions that can help them better manage their time and resources. The use of writing tools, such as reference management software and sophisticated word processing applications, has become increasingly common to improve productivity. In addition, an in-depth understanding of research methodologies and effective writing techniques has also become crucial to meet the set academic standards. Thus, efficiency in scientific writing is not only a practical necessity but also an important part of academic skill development that will support students' future success. This service focuses on developing e-modules for the use of AI (Artificial Intelligence) in writing scientific papers for students of the Indonesian Language and Literature Education study program. Through the implementation of workshops and the creation of e-modules, it is expected that students will better understand digital literacy as an effort to support academics. This program is designed by combining a systematic approach, starting from coordination with mentors, planning activities, and implementation and evaluation.